Evaluasi Tingkat Kerusakan Jalan Sebagai Dasar Penentuan Perbaikan Jalan Raya Demak – Kudus KM 03 s/d KM 05 - Saiful, Muhammad Saiful Anwar; Umam, Khotibul; Saputro, Yayan Adi (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2025)
The Demak – Kudus highway, precisely at KM 03 – 05, is one of the roads connecting two important cities, namely Demak and Kudus, which are included in the Collector road classification type. Bina Marga and PCI will be used as references in this study. Based on the results of the analysis when reviewed using the Bina Marga Method, the average Priority Sequence value was obtained of 5.96 which is included in the Priority B class category, while from the results of the analysis Based on the results of the analysis when reviewed using the PCI (Pavement Condition Index) Method, the PCI value was obtained of 54 which is included in the moderate (fair) category. The highest percentage of damage occurred in Patch damage, namely with a result of (56.279%), then the second percentage occurred in Crocodile Crack damage of (26.455%), Grain Release obtained results of (14.462%), Hole damage obtained results of (0.848%), Elongated Damage obtained results of (0.795%), Block Cracks obtained results of (0.661%), Sungkur obtained results of (0.485%) and the lowest percentage occurred in the Jembul type of damage with a result of (0.015%). The results of the analysis of both methods from Bina Marga and PCI (Pavement Condition Index) concluded that the Demak - Kudus highway has a moderate level of damage (fair) and for the type of road maintenance or road maintenance actions, a routine/periodic maintenance program can be carried out.